2014
DOI: 10.1111/jpi.12141
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin improves cerebrovascular function and decreases oxidative stress in chronically hypoxic lambs

Abstract: Chronic hypoxia during gestation and delivery results in oxidative stress and cerebrovascular dysfunction in the neonate. We assessed whether melatonin, a potent antioxidant and potential vasodilator, improves the cerebral vascular function in chronically hypoxic neonatal lambs gestated and born in the highlands (3600 m). Six lambs received melatonin (1 mg/kg per day oral) and six received vehicle, once a day for 8 days. During treatment, biometry and hemodynamic variables were recorded. After treatment, lambs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 93 publications
2
27
0
1
Order By: Relevance
“…At birth, all animals showed similar biometric variables as previously reported . Further, blood gases were similar between groups at 3 days old (data not shown), and these values were preserved until the end of the experimental protocol (Table ).…”
Section: Resultssupporting
confidence: 83%
“…At birth, all animals showed similar biometric variables as previously reported . Further, blood gases were similar between groups at 3 days old (data not shown), and these values were preserved until the end of the experimental protocol (Table ).…”
Section: Resultssupporting
confidence: 83%
“…Recently, we have shown that melatonin increases the enzymatic antioxidants mechanisms and improves pulmonary endothelial function associated with a slight increase of the luminal radius of pulmonary arteries [70]. Interestingly, the same treatment also improved vascular function and decreased oxidative stress in the neonatal brain [95].…”
Section: Perinatal Cardiovascular Responses and Treatmentmentioning
confidence: 96%
“…Indeed there is evidence that MLT acts directly on vasculature to mediate blood flow to various vascular beds including the brain, to stabilize blood brain barrier integrity [33] , prevent endothelial cell dysfunction [34] , decrease nitric oxide and VEGF production, and suppress ischemia-induced cerebral edema [35] . Furthermore, neonatal treatment with oral MLT improves cerebral vascular function in chronically hypoxic newborn lambs by increasing cerebral blood flow and improving vascular function [36] . In this study, we have further characterized the role of MLT by showing that it protects the structural integrity of the cerebral vasculature via antiapoptotic actions, and by maintaining the normal cell contact of astrocytes and pericytes with the microvessel wall in the white matter of the FGR brain.…”
Section: Discussionmentioning
confidence: 99%